1988
DOI: 10.1136/jnnp.51.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of headache in the Republic of San Marino.

Abstract: SUMMARY An epidemiological survey on headache was performed in the Republic of San Marino, which is the smallest independent State in the world, located near the Adriatic Coast, within Italy. Among a random sample of 1500 inhabitants over 7 years of age the frequency of headache, severe headache and migraine in the previous year was 35 3%, 12-2%, 9-3% respectively for men, and 46-2%, 20-6%, 18% for women. The most common factors reported to provoke headache were emotional stress, physical strain, lack of sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
27
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
(1 reference statement)
10
27
3
Order By: Relevance
“…These sources of bias are regression dilution bias arising from the fluctuation on blood pressure in each individual person 42 and the failure of some studies to adjust for age in the statistical analysis, which introduces bias because blood pressure increases with increasing age but the prevalence of headaches declines. 9,12,16,20 Whether these factors are sufficient to account for the absence of an association in many cross-sectional studies is uncertain. The conclusion that the 4 classes of blood pressure-lowering drugs reduce the prevalence of headache by about a third (whatever the mechanism) is firm, but the issue of whether higher blood pressure per se causes headache remains unresolved.…”
Section: Law Et Al Headaches and Blood Pressure-lowering Drugs 2303mentioning
confidence: 99%
See 1 more Smart Citation
“…These sources of bias are regression dilution bias arising from the fluctuation on blood pressure in each individual person 42 and the failure of some studies to adjust for age in the statistical analysis, which introduces bias because blood pressure increases with increasing age but the prevalence of headaches declines. 9,12,16,20 Whether these factors are sufficient to account for the absence of an association in many cross-sectional studies is uncertain. The conclusion that the 4 classes of blood pressure-lowering drugs reduce the prevalence of headache by about a third (whatever the mechanism) is firm, but the issue of whether higher blood pressure per se causes headache remains unresolved.…”
Section: Law Et Al Headaches and Blood Pressure-lowering Drugs 2303mentioning
confidence: 99%
“…4 Subsequent explanations were that anger-or anxiety-induced hyperventilation may both cause headache and raise blood pressure. 5,6 Cross-sectional studies have generally shown no association between blood pressure and headache, 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] reinforcing the prevailing view that there is no link with headache 22 or that, if there is, the headaches are attributable to anxiety and tension induced by being told one has "hypertension." 23 Recently, an editorial asked, "Why does the hypertension headache myth persist?"…”
mentioning
confidence: 99%
“…‘do you suffer from headache?’‘do you have intense headache?’, ‘do you have repeated headaches?’, etc). In studies reporting the 1‐year prevalence of headache with a screening question specifying some headache degree, the prevalence rates vary between 29 and 49% among adults [40–43]. In those with higher figures [11,44], the exact way of questioning has not been given.…”
Section: Discussionmentioning
confidence: 99%
“…One or a few screening questions that limit the study population are commonly used [e.g., 212]. Validation of the method is always required in epidemiological surveys [1, 13], and it should include evaluation of headache prevalence among screen-negative individuals if a screening question is used.…”
Section: Introductionmentioning
confidence: 99%